2022
DOI: 10.3389/fneur.2022.964454
|View full text |Cite
|
Sign up to set email alerts
|

An integrated intervention of computerized cognitive training and physical exercise in virtual reality for people with Alzheimer's disease: The jDome study protocol

Abstract: IntroductionAlzheimer's disease is a neurodegenerative syndrome characterized by cognitive deficits, loss of daily functions, and mental and behavioral disorders, which cause stress and negatively affect the quality of life. Studies in the field suggest that combining cognitive training with physical activity can reduce the risk of developing the disease and, once neurodegeneration has begun, it slows its progress. In particular, virtual reality and augmented reality administer cognitive stimulation while prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Deijle et al ( 16 ) and Lapointe et al ( 18 ) have found that simple PFT has no impact on cognitive function in ischemic stroke patients. Cognitive function improvement is only observed when combining cognitive training with procedural guidance in addition to physical exercise ( 39 , 40 ). The study by Shang et al ( 19 ) on GT indicates that it may not only improve motor function but also potentially enhance cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Deijle et al ( 16 ) and Lapointe et al ( 18 ) have found that simple PFT has no impact on cognitive function in ischemic stroke patients. Cognitive function improvement is only observed when combining cognitive training with procedural guidance in addition to physical exercise ( 39 , 40 ). The study by Shang et al ( 19 ) on GT indicates that it may not only improve motor function but also potentially enhance cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of mental exercise to the AD brain are uncertain, but cognitive stimulation may be helpful, particularly in MCI patients [ 351 , 352 , 353 , 354 ]. Studies are underway or planning to evaluate the combination of mental and physical challenges using virtual reality in persons with mild AD [ 355 , 356 ].…”
Section: Mental and Physical Activitymentioning
confidence: 99%
“…Recently, computer games are gaining scientific interest as a cognitive training tool due to their playful nature. 4 Certain computer game training has been shown to yield positive effects on untrained tasks, commonly referred to as a transfer effect.…”
Section: Introductionmentioning
confidence: 99%